Potential Maternal Risk Factors for Low Birth Weight in Indonesia: A Systematic Review - Nurwati, Yuni; Hardinsyah, Hardinsyah; Marliyati, Sri Anna; Santoso, Budi Iman; Anggraini, Dewi (Jurnal Gizi dan Pangan, 2023)
This review was conducted with the aim of summarizing the articles on the potential maternal risk factors for Low Birth Weight (LBW) in Indonesia. All observational studies conducted in Indonesia between 2010 and 2022 were thoroughly reviewed in this study. The articles were retrieved from "PubMed", "ScienceDirect", "Web of Science", and "Garuda". The retrieval was supplemented by snowball sampling technique. This review was constructed according to the PRISMA guidelines and the quality of the articles was assessed according to the STROBE guidelines. Of the 129 articles, only 12 articles met the inclusion criteria. Maternal variables such as education (50%), household wealth (33.3%), nutritional status (33.3%), age (25%), pregnancy complications (25%), marital age (16.7%), gestational weight gain (16.7%), ANC visit (16.7%), weight at third trimester (16.7%), twin birth (16.7%), birth interval (16.7%), iron supplementation (8.3%), parity (8.3%), and anemia status (8.3%) were found to be the risk factors for LBW incidence. This review found that almost all potential maternal risk factors contributing to LBW are preventable. It may help policy makers to design a more effective LBW prevention intervention and early risk identification for pregnant women. Appropriate follow-up by health workers for clinical intervention will also help to improve their pregnancy outcomes.